ISLAMIC EDUCATION OF CHILDREN WITH PARENTS AS INDONESIAN MIGRANT WORKERS (Case Study in Karangwotan Village, Pati, Central Java) - Suciati Suciati (P3M STAIN Kudus, 2016)
Many parents who decided to work abroad as International migrant workers. They work for financial fulfilment. On the other hand, their children do not get more attention from them because the children are usually left by father/mother or both of them to work abroad and the children are at home just with their mothers or grandparents. This qualitative research was conducted in Karangwotan village, Pati, Central Java. The data showed three result: (1) problems faced by the children with parents as immigrant in getting Islamic education are that they do not have the real model in the family and there was no father/mother or both of them who teach and educate in the family; (2) there is just little parents’ influence to children’s islamic education. It is just such kind of order, suggestion and advice; and (3) for getting the islamic education,  the children with parents as immigrant workers join several islamic programs. They are Taman Pendidikan Qur’an (TPQ) or Program of Qur’an Education, Madrasah Ibtidaiyyah or Islamic Elementary School, and the islamic courses.